To rewrite the equation \(\frac{5}{2x-8} - 1 = 9\) as two equations joined by "and," we first isolate the rational expression and then handle the condition for the variable.
-
Start with the original equation:
\(\frac{5}{2x-8} - 1 = 9\) -
Rearranging gives us:
\(\frac{5}{2x-8} = 10\) -
Now we express it as two equations:
\(\frac{5}{2x-8} = 10\) and \(2x - 8 \neq 0\) (to avoid division by zero)
From \(2x - 8 \neq 0\), we find \(x \neq 4\).
Thus, the correct response is:
\(\frac{5}{2x-8} = 10\) and \(x \neq 4\) (not present in the options you provided).
Therefore, based on the provided options, the correct transformation would be:
\(\frac{5}{2x-8} - 1 = 9\) and \(x \neq 4\).